Efficacy of R‐BAC in relapsed, refractory mantle cell lymphoma post BTK inhibitor therapy. (3rd February 2020) - McCulloch, Rory; Visco, Carlo; Eyre, Toby A.; Frewin, Rebecca; Phillips, Neil; Tucker, David L.; Quaglia, Francesca M.; McMillan, Annabel; Lambert, Jonathan; Crosbie, Nicola; Rule, Simon
Summary: Patients with mantle cell lymphoma progressing on Bruton's tyrosine kinase inhibitor (BTKi) have very poor prognosis and there is currently no standard of care. In this retrospective cohort study, patients progressing on BTKi received R‐BAC (rituximab, bendamustine, cytarabine). Overall response rate was 83% (complete response 60%) and 31% were bridged to allogeneic stem cell transplant (alloSCT). Median progression‐free survival was 10.1 months (95% confidence interval (CI) 6·9–13·3) and median overall survival was 12·5 months (95% CI 11·0–14·0). In those consolidated with alloSCT only one patient relapsed. R‐BAC demonstrates a high response rate in the post‐BTKi setting and in transplant eligible patients is an effective bridge to alloSCT.